EMPLOYEES’ PSYCHOLOGICAL HOPE AND ORGANIZATIONAL COMMITMENT IN MAJOR OIL AND GAS COMPANIES IN THE NIGER DELTA REGION OF NIGERIA - B. M. Nwibere; Worlu, G.O. (Scholars Digest Publishing, 2024)
This research investigates the correlation between employees' psychological hope and their organisational commitment. The study encompasses a sample of 280 managerial and non-managerial employees randomly drawn from ten prominent oil and gas companies situated in the Niger Delta Region of Nigeria. Employing a quasi-experimental research design, data collection was conducted via a cross-sectional survey deemed most suitable for the administrative sciences. Data analysis employed the Spearman rank correlation coefficient and multiple regression model, utilising Statistical Package for Social Sciences (SPSS) version 15. The results reveal a positive and significant association between employees' psychological hope and organisational commitment within the major oil and gas companies in the Niger Delta region of Nigeria. Specifically, employees' willpower and way power were identified as exerting a favourable and statistically significant impact on their affective commitment, normative commitment, and continuance commitment, respectively, within these organisations. In light of these findings, the study concludes that employees' psychological hope significantly contributes to bolstering organisational commitment within major oil and gas companies in the Niger Delta region of Nigeria. Particularly, the study emphasises the pivotal roles played by employees' willpower (agency) and way power (pathways) in augmenting their affective commitment, normative commitment, and continuance commitment within these organisations. Consequently, the study underscores the imperative for managers in Nigerian Oil and Gas industry to adeptly manage employees' psychological hope to fortify their commitment to the organisation. Moreover, the study deliberates on additional theoretical and managerial implications for effectively nurturing employees' hope and enhancing organisational commitment in the workplace, with specific reference to the Nigerian Oil and Gas industry.
Keywords: Higher Education, Research and Innovation Efficiency, Funding, Scientific Personnel, Collaboration, Material and Technical Support, Institutional Support, Student Involvement, External Infrastructure, Uzbekistan.